Organising the ERUA Open Science Meet-Ups: Methods, Experiences and Lessons from the First Ten Months - Heber, Maximilian (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
The field of Open Science is subject to constant change and expansion. In order to stay up to date, exchange is paramount – not only within universities, but also within larger spheres, such as academic alliances. This paper analyses the development of a format of international Open Science-related exchange called “ERUA Open Science Meet-Ups” within the Re:ERUA project (research trajectory of the European Reform University Alliance). We will look at in which contexts the format came to be, how we got the format started and which measures of promotion and dissemination we took. Moreover, we will discuss the individual sessions’ scope and provide insight into which lessons we learned when performing the Open Science Meet-Ups. Specific recommendations for everyone wanting to set up a similar format as well as an outlook on future sessions will conclude the paper.